THE YIJING AND THE CRISIS OF WESTERN TRADITION - Ernest Ženko (Srpska Politička Misao)
In the article author follows a view that although rational thinking can be found in all literate societies around the globe, differences between cultures develop to a certain degree also from basic distinctions between philosophical ways of thinking. In this sense, the Yijing, or The Book of Changes, classical text not only characterizes the basic mode of Chinese philosophical thinking, but also influences past and present Chinese culture. The Yijing, however, did not only influence Chinese contexts, but from the 18th century on, its impact was felt also in the West. To Jesuit translators, Leibniz and C. G. Jung, and even to 20th century physicists, artists or musicians, this ancient text had always something relevant to say. The more so in times of crisis, when it became evident that it is better to escape one’s own culture and to look for answers elsewhere; in a wholly different tradition. It seems, however, that the reception of the Yijing in the West went full circle; from being an exotic and mystical text from an unknown and foreign practice, to an important corrective of a Western tradition that found itself in crisis during the twentieth century, to the global culture industry.